Privacy, obfuscation, and propertization - Doyle, Tony (IFLA journal, 2018)
As our digital wake ripples out, big data is standing by to ride it, applying its analytics to make unnerving inferences about our characters, preferences, and future behavior. This paper addresses the challenge that big data presents to privacy. I examine what are perhaps the two most promising attempts to repel big data’s attack on privacy: obfuscation and the “propertization” of personal information. Obfuscation attempts to throw data collectors off our digital trail by confusing or misleading them. Propertization calls for treating personal information as intellectual property and would require that data holders compensate data subjects for any secondary use. I try to show that both defenses largely fail. I conclude that privacy is a lost cause and that we should call off the attempts to defend it from the moral point of view. I close with some thoughts about what this all means for libraries.